Parenting Patterns in Shaping Children's Islamic Character - Helena, Helena; Firsya, Rahmatul Hasni; Fitriani, Fitriani (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
Basically, each family's parenting style varies from one family to another. Differences in parenting styles in families make each individual or child have a different character. This research aims to analyze the parenting patterns applied by parents in shaping children's Islamic character. This research uses a qualitative method with a phenomenological type of research. Research data was taken through direct interviews with six informants, three parents and three children. All interview data was then analyzed using the Miles and Huberman analysis technique. Overall, this research found that there are three parenting patterns for parents in cultivating their children's Islamic character at home with different characteristics. The three parenting styles and their characteristics are: i) democratic has the characteristics: providing rules that suit the child's needs, parents always providing direction and understanding towards the child, and an attitude of openness between parents and children. ii) authoritarianism has characteristics: parents apply absolute rules to their children, parents emphasize an attitude of submission and obedience to established rules, parents' parenting style is harsh and emotional. iii) permissiveness has the following characteristics: parents allow their children to make their own decisions, parents have few rules, and parents are tolerant, their attitude is accepting of the children's wishes and encouragement. The results of this research can be used as initial data for subsequent researchers in studying different issues related to this problem as well as various other issues relevant to this concept.